Lim√x+1 -2 /x-3 x-->3+
Soluções para a tarefa
Respondido por
1
Lim [ √(x+1) -2]/(x-3)
x-->3⁺
Lim [ √(x+1) -2][ √(x+1) + 2]/(x-3)[ √(x+1) +2]
x-->3⁺
Lim [ √(x+1)² -2²]/(x-3)[ √(x+1) +2]
x-->3⁺
Lim [ x+1 - 4]/(x-3)[ √(x+1) +2]
x-->3⁺
Lim [ x-3]/(x-3)[ √(x+1) +2]
x-->3⁺
Lim 1/[ √(x+1) +2] =1/(2+2)=1/4
x-->3⁺
x-->3⁺
Lim [ √(x+1) -2][ √(x+1) + 2]/(x-3)[ √(x+1) +2]
x-->3⁺
Lim [ √(x+1)² -2²]/(x-3)[ √(x+1) +2]
x-->3⁺
Lim [ x+1 - 4]/(x-3)[ √(x+1) +2]
x-->3⁺
Lim [ x-3]/(x-3)[ √(x+1) +2]
x-->3⁺
Lim 1/[ √(x+1) +2] =1/(2+2)=1/4
x-->3⁺
Perguntas interessantes
Matemática,
11 meses atrás
História,
11 meses atrás
Geografia,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás